Spatio-temporal assessment of changing annual and seasonal climate patterns over the major climatic zones of Pakistan / Haris Uddin Qureshi, Syed Muzzamil Hussain Shah, Fang Yenn Teo - Qureshi, Haris Uddin; Hussain Shah, Syed Muzzamil; Fang, Yenn Teo (2023)
The extensive impacts of climate change on the ecology and the environment have made it one of the biggest challenges being faced by the humanity today. Apart from the temporal scale, the climate patterns also vary on the spatial scale due to the different spatial features and the latitudinal location. This necessitates investigating the changing climate patterns over the different locales to formulate a holistic climate change adaptation and mitigation strategy. Therefore, this study was conducted to briefly investigate the annual and seasonal climate trends over the major climatic zones of Pakistan during the period 1990-2022 using the MK test and Sen's slope estimator method. The results obtained from the study showed an annual mean temperature rise of about 0.1 to 1.0 °C over the Greater Himalayas and sub-Montane region, and about 0.15 to 1.2 °C over the central, southern, and the coastal parts of the country, while a declining trend was found over the Western Highlands during the study period. Seasonally, the spring season was found to be the warmest among all seasons in the country. For the summer season, a declining trend was found over the Greater Himalayas and Western Highlands, while warming increased over the other climatic zones. For the winter season, the temperature rose by about 0.1 to 1.0 °C over the Greater Himalayas and northern Balochistan, and by about 0.1 to 0.2 °C over the coastal zones. For annual precipitation, an increasing trend was found over the majority of the selected stations, whereas for the summer monsoon, a declining trend was found over the Greater Himalayas, while the other zones witnessed a significant rising trend, with the highest increment noted over the Western Highlands (100-300 mm), and about 50-150 mm in central Punjab and the lower Indus plain. For winter precipitation, the Greater Himalayas observed an upward trend (0.3-0.9 mm/year), while the southern and coastal parts of the country witnessed a declining pattern. Based on the findings, it was established that the climate patterns have varied greatly on the spatial scale over Pakistan, which necessitates the formulation of an integrated and effective climate change adaptation and mitigation strategy for the conservation of natural resources in the country.